UI/UX Design on Digilearn Application with the Iterative Design Thinking Methodology - Amalia Ristias, Arsya; Sahlan Amin, Mochamad; Agussalim, Agussalim (Information Technology International Journal, 2023)
Innovations in education and learning today are followed by advances in technology. The increasing use of online information technology has encouraged educational institutions to invest in new learning technologies such as E-Learning. E-Learning is teaching and learning that is supported and developed through technology and digital media, and is also a form of the concept of distance learning or distance learning. By understanding what they are complaining about, researchers as product designers can empathize with them, so that they can define their problems perfectly, create brilliant ideas, design solutions based on ideas, and try the results of these designs on target users. Therefore, researchers learn that empathy is the key to the success of a product because in the end, the product will be used by the users that the designer has expected.